2010
DOI: 10.14301/llcs.v1i3.93
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cognitive ability and adult academic attainment: evidence from three British cohort studies

Abstract: This paper examines the association between general cognitive ability directly measured at age 10/11, and adult academic attainment in three British birth cohorts born in 194610/11, and adult academic attainment in three British birth cohorts born in , 195810/11, and adult academic attainment in three British birth cohorts born in , and 1970

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The strongest evidence relates to the predictive power of early verbal and visual motor skills and early behaviour regulation, which are significant predictors of educational and occupational attainment at age 42, as well as income. The study confirms previous evidence regarding the role of early cognitive competences as predictors of adult outcomes (Claessens et al, 2009;Ritchie & Bates, 2013;Fitzpatrick et al, 2015;Schoon, 2010). In addition, it confirms the importance of behaviour-regulatory competences (Moffitt et al, 2011;Washbrook et al, 2013;Hammer et al, 2018;Duckworth et al, 2019) over and above cognitive competences and socio-economic risk exposure.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The strongest evidence relates to the predictive power of early verbal and visual motor skills and early behaviour regulation, which are significant predictors of educational and occupational attainment at age 42, as well as income. The study confirms previous evidence regarding the role of early cognitive competences as predictors of adult outcomes (Claessens et al, 2009;Ritchie & Bates, 2013;Fitzpatrick et al, 2015;Schoon, 2010). In addition, it confirms the importance of behaviour-regulatory competences (Moffitt et al, 2011;Washbrook et al, 2013;Hammer et al, 2018;Duckworth et al, 2019) over and above cognitive competences and socio-economic risk exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Previous research on the role of childhood competences as predictors of later outcomes has mostly focused on specific indicators, such as general IQ (Schoon, 2010;Cukic et al, 2017) or self-control (Moffitt et al, 2011;Duckworth et al, 2019). Alternatively, broader concepts such as non-cognitive or soft skills, indicated by composite measures, have been used (Heckman et al, 2006;Heckman & Kautz, 2012;Liu, 2019).…”
Section: Early Childhood Competencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic and cognitive performance share many of the same risk factors (e.g., cerebrovascular injury, chronic anemia, socioeconomic status); however, they are unique constructs. In the general population, environmental factors account for a greater amount of variance in academic performance than cognitive ability ( 15 , 16 ). This is particularly relevant for students with SCD, as they are more likely to be raised in single-parent families, live in low-income resource-poor neighborhoods, and attend financially disadvantaged school systems ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This predictive capacity is the main reason why intelligence is relevant to sociological analysis (Deary 2012). Intelligence predicts educational attainment at all ages (Connelly and Gayle 2019;Deary et al 2007;Feinstein 2003;Marks 2014Marks , 2021Nash 2001;Ritchie 2015;Schoon 2010;Strenze 2007), even in the relatively few studies that have found some weakening of its statistical effects over time (Machin and Vignoles 2004;Galindo-Rueda and Vignoles 2005). Intelligence predicts social mobility (Breen and Goldthorpe 2001;Deary et al 2005;Johnson, Brett, and Deary 2010a;Nettle 2003;Strenze 2007), partly but not wholly because it mediates between class of origin and class of destination (Betthäuser, Bourne, and Bukodi 2020;Bourne et al 2018;Deary et al 2005;Johnson et al 2010a;Marks 2020).…”
Section: Introductionmentioning
confidence: 99%